Relevansi P5-PPRA dengan Pendidikan Perspektif Syekh Nawawi Al Bantani - Khayati Muflikha, Ila; Maskur Musa, Muhammad (Indonesian Journal of Islamic Elementary Education, 2024)
Character education needs to be based on religion and associated with education, as is the opinion of one of the scholars, namely Sheikh Nawawi Al-Bantani, regarding moral education. This research aims to analyze the relevance of current character education to the thoughts of Sheikh Nawawi Al-Bantani. The method used in this research is literature study. Researchers collect literature relevant to this research such as from scientific articles, books and other sources. The data obtained was then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of this research show that Sheikh Nawawi Al Bantani’s thoughts are very relevant to the current concept of Indonesian education, namely the independent curriculum, which includes the Project for Strengthening the Pancasila Student Profile (P5) and the Rahmatan lil Alamin Lesson Profile (PPRA). This relevance is related to the dimensions of P5-PPRA such as; Be civilized (ta’addub); b) Exemplary (qudwah); c) Citizenship and nationality (muwatanah); d) Taking the middle path (tawassut); e) Balanced (tawazun); f) Straight and firm (I’tidal); g) Equality (musawah); h) Deliberation (shura); i) Tolerance (tasamuh); j) Dynamic and innovative (tatawwur wa ibtikar). From these dimensions, it can be seen that P5-PPRA links Pancasila values with moral cultivation.